2022
DOI: 10.1155/2022/4182853
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of Retroperitoneal Laparoscopic Radical Nephrectomy on Renal Cell Carcinoma, the Influence of Renal Function, and the Influencing Factors of Recurrence

Abstract: Renal cell carcinoma is abbreviated as renal carcinoma, and its clinical symptoms are basically hematuria, lumbago, and abdomen bump. As people’s lifestyles change, the incidence of renal carcinoma continues to rise due to factors such as smoking and obesity. At present, surgical treatment is mostly used in clinical practice. Traditional open radical nephrectomy (ORN) is one of the main methods for clinical treatment of renal carcinoma. However, due to its large wound and large amount of intraoperative blood l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Its advantages include minimal invasiveness, less post-operative pain, faster recovery, and a shorter hospital length of stay. 3,4 Moreover, laparoscopic partial nephrectomy provides better renal functional preservation without surgical complications. 5 Currently, general anesthesia (GA) alone is the most frequently-used approach to the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Its advantages include minimal invasiveness, less post-operative pain, faster recovery, and a shorter hospital length of stay. 3,4 Moreover, laparoscopic partial nephrectomy provides better renal functional preservation without surgical complications. 5 Currently, general anesthesia (GA) alone is the most frequently-used approach to the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%